Role of core needle biopsy as a first-line diagnostic tool for thyroid nodules: a retrospective cohort study - Min Ji Hong; Dong Gyu Na; Soo Jin Kim; Dae Sik Kim (Ultrasonography, 2018)
Purpose The purpose of this study was to evaluate the diagnostic efficacy of fine-needle aspiration (FNA), core needle biopsy (CNB), and combined FNA/CNB for the first-line diagnosis of thyroid nodules. Methods A total of 782 consecutive nodules that underwent simultaneous FNA and CNB were analyzed in this study. We compared the rate of inconclusive results and the diagnostic values for malignancy among FNA, CNB, and combined FNA/CNB. Results CNB showed a lower rate (10.2%) of inconclusive results than FNA (23.7%) (P<0.001). Combined FNA/CNB showed a lower rate (6.5%) of inconclusive results than FNA (all nodules, P<0.001; macronodules, P<0.001; and micronodules, P<0.001, respectively) or CNB (all nodules, P<0.001; macronodules, P<0.001; and micronodules, P=0.003, respectively). Combined FNA/CNB and CNB showed significantly higher sensitivity, accuracy, and diagnostic performance for malignancy as defined by criterion 1 (Bethesda category VI) or criterion 2 (Bethesda categories IV/V/VI) than FNA (P<0.001). However, there was no significant difference in the sensitivity, accuracy, or diagnostic performance between combined FNA/CNB and CNB (with criterion 1, P=0.063, P=0.063, and P=0.412, respectively; with criterion 2, P=0.500, P=0.500, and P=0.348, respectively). Conclusion CNB was found to be more effective than FNA for the diagnosis of thyroid nodules, and its sensitivity and diagnostic performance for malignancy were similar to those of combined FNA/CNB. CNB has the potential to be an effective alternative first-line diagnostic tool for thyroid nodules when performed by an experienced operator.